PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC PERIODE 2010-2014 - DWI KURNIAWAN, ARIS (Jurnal Akuntansi AKUNESA, 2016)
The aim of this study is to examine the effect of good corporate governance on financial performance of Corporate Governance Perception Index (CGPI) listed companies. The samples are listed in Corporate Governance Perception Index (CGPI) report by the Indonesian Institute for Corporate Governance (IICG). The research uses multiple linear regression.  This study shows that the implementation of good corporate governance is not absolutely affecting return on equity (ROE). The implementation of control variable (size) is not absolutely affecting return on equity (ROE).    Keywords: Corporate Governance Perception Index (CGPI), size, return on equity (ROE)